2020
DOI: 10.1093/asj/sjaa337
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Health Complaints in Women Undergoing Explantation of Breast Implants

Abstract: Background Concerns about the safety of silicone breast implants have existed for years, but a causal relationship between systemic complaints and SBI has not been proven. Nevertheless, women are worried and even request explantation. Objectives This study aimed to review the explantation procedures performed, focusing on patient-reported symptoms preoperatively, the effect of explantation, and the effect of breast reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, cluster A was the most consistent with the majority of the reported breast implant illness symptoms in our study and in the existing literature. 9,10 Although specific conclusions cannot be drawn from the two clusters, their existence could be telling in Plastic and Reconstructive Surgery • December 2022 large-scale prospective trials when more detailed knowledge of breast implant illness emerges. Despite their reintroduction to the market in 2006, additional secondary analysis of the U.S. Food and Drug Administration's postapproval studies on nearly 100,000 women with breast implants demonstrated associations between silicone implants and increased rates of autoimmune issues and systemic harms.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cluster A was the most consistent with the majority of the reported breast implant illness symptoms in our study and in the existing literature. 9,10 Although specific conclusions cannot be drawn from the two clusters, their existence could be telling in Plastic and Reconstructive Surgery • December 2022 large-scale prospective trials when more detailed knowledge of breast implant illness emerges. Despite their reintroduction to the market in 2006, additional secondary analysis of the U.S. Food and Drug Administration's postapproval studies on nearly 100,000 women with breast implants demonstrated associations between silicone implants and increased rates of autoimmune issues and systemic harms.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the implants improves health complaints in half of the patients [ 35 ]. A tertiary ABR could offer a solution for these women [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only local pain to the chest, as in capsular contracture, but also widespread pain, as in fibromyalgia, has been reported in relation to breast implants. 1 , 9 We found that both pain intensity and pain-related disability measured with the CPGS were significantly higher in BII patients than in controls. Previous MRI studies have led to the understanding that chronic pain patients display brain alterations regarding brain function and structure.…”
Section: Discussionmentioning
confidence: 66%
“…There is no objective method to assess the harmfulness of SBIs and therefore no targeted therapy is available, except the permanent removal of the implants. 9 In the majority of cases, this treatment is not reimbursed by health insurance, as a result of which patients do not receive the desired help and do not feel taken seriously. On the other hand, women are at risk of undergoing unjustified medical interventions, which can have both physical and psychological consequences.…”
mentioning
confidence: 99%